(untitled) (BIMRAD Journal, 2025)
Latest technology is the most modern, smart and advance technology and which is usually considering as an effective and useful tools to monitoring, managing and decision making to optimize maritime resource extraction, ocean health and develop smart maritime organization by preserving environment, safety and security in modern era. Latest and smart technology facilitates to analyze huge data, track vessels or marine resources by ensuring environmental issues intact. Artificial Intelligence (AI) and other smart-powered solution with advance sensors, satellite images, smart models, etc. are supreme in furnishing scientists and researchers with the tools essential for real-time surveillance, tracking and early recognition of maritime safety or security issues, vessel traffic, surveillance, extending their observational reach and maritime warfare. AI, Machine Learning (ML) and other smart technology will lead and dictate the future to preserve the sea and its resources for the mankind and safe operation of maritime industry by ensuring safety and security. We can utilize AI and other advance technology at its full potential to make the health of oceans better and solve many maritime security and safety issues as we don’t know but which may rise in future. We need to train our man and future generation with the knowledge and skill of AI and other advance technology in 21st century to develop modern maritime sector including Navy. We need to accrue knowledge, intelligence and wisdom along with useful skill to build purposeful navy for prosperous Bangladesh. It is an analytical study to evaluate that the latest technology is the best and effective option to enhance maritime sector and develop future and modern navy. BIMRAD Journal VOLUME 5, ISSUE 1, DEC 2024; PP-40-62